Geometric Characterizations of Non-Uniform Structure I Methane Hydrate Behaviors Under Pressure - Samuel Mathews; Xiaodan Zhu; André Guerra; Phillip Servio; Alejandro Rey (Crystals)
Gas hydrates have been identified as one of the leading candidates for future energy sources. According to conservative estimates, the energy contained in natural hydrates is double that of the fossil fuel that has been explored. This substantial energy storage motivates the investigation of natural hydrates. Prior research on mechanical/material properties has assumed that the lattice would be the smallest unit and averaged all the features within the lattice, disregarding smaller-scale geometric properties. We investigated the geometric features of sI methane hydrate under pressure. The sI methane hydrate is made up of two kinds of cages (polyhedrons) with two kinds of faces (polygons), and the vertices of the polygons are occupied by water oxygen atoms. Based on these three categories, we examined the cage integrity, face deformation, and water oxygen atom bond lengths and angles within and beyond the stability limits. The presence of forbidden zones was confirmed in bond length and angle distributions, validating the effects of geometric features. The predictive nature of water molecule angular displacement with pressure was validated. This multiscale computational materials science methodology describes and defines the range of the elastic stability of gas hydrates, a crucial contribution to energy materials science and engineering.